Probation practice, desistance and the penal field in Norway - Todd-Kvam, John (Criminology & criminal justice, 2022)
While Scandinavia in general and Norway in particular have been the focus of much criminological interest, the work of probation has largely been overlooked in favour of prisons. This article seeks therefore to contribute to our knowledge of Norwegian penality and desistance by analysing how probation caseworkers describe their practice. Caseworkers have a relational, contextualised understanding of probation clients and the challenges they face. That being said, even in a Scandinavian welfare state, caseworkers see the process of reintegration and change as difficult, highlighting a lack of human and social capital and the challenges of navigating an increasingly complex and impersonal welfare apparatus.